Elsieskraal: River restoration as urban catalyst - Moss, Dennis (School of Architecture, Planning and Geomatics, 2024)
Water is one of the main issues of the 21st century. Climate change and biodiversity loss, driven by human development, underscore the need to restore a harmonious relationship with the planet. The current global action plan to achieve this is the United Nations' 2030 Agenda, which outlines specific goals (SDGs) to promote sustainable development. Sustainable development cannot be achieved without “significantly transforming the way we build and manage our urban spaces” (United Nations, 2015). As urban practitioners, we have a large role to play in SDG 11, with its mission to “make cities and human settlements inclusive, safe, resilient, and sustainable” (United Nations, 2015). This requires a comprehensive understanding of the human- and natural capital available to us, and the ways in which these resources can be employed at different scales and varying contexts. With half of the world's population now living in cities, it is in the urban environment where intervention is most crucial. Africa, in particular, is set to undergo rapid urbanisation, with estimates that its population of 1.1 billion will double by 2050 (WWF, 2020, p. 4). This will require strategic planning. Rather than contributing to the problem, resilient cities can be “the source of solutions” (UN General Assembly, 2016, p. iv). How we manage water will be key to this success. This research project will explore the effects that river restoration can have on urban transformation. The focus will be the Elsieskraal River, which flows from the Tygerberg Hills to the Black River, through “the most diverse and densely populated range of suburbs” in Cape Town (Brown, 2009, p. 135). A series of design interventions, guided by a multi-disciplinary, systems-based approach, and informed by theory, best practice and policy, will test the potential catalytic impact of river restoration in an urban setting.